SISTEM DETEKSI POLUSI DI FAKULTAS TEKNOLOGI INFORMASI UNIVERSITAS HASYIM ASY’ARI DENGAN METODE FUZZY LOGIC - Permadi, Ginanjar Setyo; Faruq, Muhammad (Inovate, 2022)
ir pollution is a condition where air quality decreases because it is affected bysubstances that are not harmful or harmful to the health of the human body. Airpollution is often encountered in the surrounding environment from human activitiesthat can harm and damage the health of the human body. The impact of air pollution isdamage to human health and the environment. Damage to human health can be affectedby pollutant substances that enter the body. Some of the pollutant substances mixed inthe air have well-recognized properties, so their presence in the body can certainly causediscomfort. While in the environment can cause global warming, acid rain, depletion ofthe ozone layer, and others. Then made a system that can detect air pollution. Thepollution detection system that is made works well so that it can be used to detectpollution in the form of carbon monoxide gas and dust. The data detected by the sensoris calculated using fuzzy logic. So that it can produce a fuzzy output value of174.21655744439 which means that the air quality in the research location is nothealthy. Keywords: air pollution, fuzzy logic, carbon monoxide, dust.